Candi, Paduan Artistik Antara Pemujaan Nenek Moyang Indonesia Dengan Kuil India - Muhammad Arif Jati (Institut Seni Indonesia Surakarta, 2006)
Temple is an ancient architecture heritage of Indonesian classic period, move in Hindust and Budhist culture about V until XV century. Temple is one of culture aspect influence India country together with movement of Hindust and Budhist in Indonesia. The form of temple got an influence from Indian, but the world of temple it self not from India. Foremely the people thing that temple is the place burial of King, whereas it is as a King servitude symbol.From the explanation above can be sumarized that temple is the artistic combination betwen an cestors worship and Indian stupa. Keywords : Candi (temple), place burial of King, an cestors worship and Indian stupa.